The rule of Brigadier Oupa Gqozo in Ciskei: 4 March 1990 to 22 March 1994 - White, Colin Stewart (Rhodes University, Faculty of Humanities, Department of History, 2009)
Although the history of the Eastern Cape has been recorded from the eighteenth century, virtually nothing has been written about the political entity known as the independent Republic of Ciskei (1981 "“ 1994). This hiatus in our history, coupled with the fact that many of the official records of that period have been destroyed, make it imperative that the role-players of the period be contacted and their evidence be recorded before it is lost to prosperity. This need has motivated the writing of the thesis. The thesis commences with a brief description of the early history and constitutional development of Ciskei. It then has a substantial chapter on Lennox Sebe, the ruler of Ciskei from 1973 to 1990, who is described as the catalyst of Gqozo's coup d'état. This is followed by a short personal biography of Oupa Gqozo, and his rise to the position of Brigadier in the Ciskei army. On 4 March 1990 Gqozo led the coup by the Ciskei Defence Force that dethroned Sebe. At the outset he ruled in an exemplary manner, but after being misled by South African agents he turned against the African National Congress and his own people. When he established his own party, the African Democratic Movement, and re-instated the hated headman system, civil war followed in Ciskei. Separate chapters in the thesis relate the various traumatic events that occurred during Gqozo's reign: the killing of Anton Guzana and Charles Sebe; the dismissal of the senior officers of the CDF; the strife during 1991/2; the Bhisho Massacre; its aftermath; the mutiny by the security forces and Gqozo's resignation on 22 March 1994. The thesis concludes that although Brigadier Gqozo respected the rule of law, and was free of corruption, he was devoid of the necessary academic qualifications, experience and ability, including the necessary insight and foresight, to rule a country. He became paranoid about his own safety and the possible overthrow of his government, and he was too easily swayed by others. In short, Gqozo was inept, rather than evil.
Keywords: Gqozo, Oupa; Sebe, L L W (Lennox L W); Massacres -- Bisho (South Africa); Ciskei (South Africa) -- History -- 20th century; Ciskei (South Africa) -- Politics and government -- 20th century